Rate of injury and subjective benefits of gravitational wellness weightlifting - Burke DT; Bell R; Al-Adawi S; Alexandroni A; Dorvlo A; Burke DP (Dove Medical Press, 2014)
David T Burke,1 Regina Bell,1 Samir Al-Adawi,2 Ariel Alexandroni,1 Atsu Dorvlo,3 Daniel P Burke4 1Emory University School of Medicine, Atlanta, Emory University, GA, USA; 2Department of Behavioral Medicine, College of Medicine and Health Sciences, 3Department of Mathematics and Statistics, College of Science, Sultan Qaboos University, Muscat, Oman; 4Georgia College and State University, Milledgeville, GA, USA Background: A preliminary study using the "gravitational wellness" weightlifting technique demonstrated this to be a unique technique for loading the musculoskeletal system with extremely high loads over short arcs. This leads to rapid weekly strength gains using 30-minute weekly training sessions. This study was designed to further assess the benefit–risk ratio of the gravitational wellness weightlifting technique. Purpose: This descriptive/retrospective study examined musculoskeletal and well-being outcomes as well as injuries reported by consecutive participants at one gravitational wellness gym. Materials and methods: All adults presenting for training at the Atlanta, Georgia, gravitational wellness system facility over a 6-month period were invited to participate. Data were obtained by telephone interview concerning the presenting complaint/objective of training, subjective outcome, weights lifted, and injuries incurred during training. Results: Of the 77 participants contacted via telephone, 92% agreed to participate (male, n=40; female, n=31). The participants ranged in age from 18 years to 69 years, with a mean age of 48.6 years. Of these, 42 (59%) presented to the gym with the objective of improving a defined musculoskeletal issue. The modal of these was chronic low-back pain. The subjects realized improvement on a 5-point Likert scale of 4.2/5 for their presenting complaint, and improved by 4.27/5 in their overall subjective health. There were no injuries. Conclusion: This study of consecutive participants at a gravitational wellness gym found that by lifting large weights over short arcs 30 minutes per week, participants significantly increased their strength, reduced their musculoskeletal pain, improve their subjective well-being, and reported a low rate of injury. Keywords: gravitational wellness system, rate of injuries, weight training, descriptive study